2014
DOI: 10.1542/peds.2013-4146
|View full text |Cite
|
Sign up to set email alerts
|

Telephone Peer Counseling of Breastfeeding Among WIC Participants: A Randomized Controlled Trial

Abstract: OBJECTIVE: The US Surgeon General has recommended that peer counseling to support breastfeeding become a core service of the Supplemental Nutrition Program for Women, Infants, and Children (WIC). As of 2008, 50% of WIC clients received services from local WIC agencies that offered peer counseling. Little is known about the effectiveness of these peer counseling programs. Randomized controlled trials of peer counseling interventions among low-income women in the United States showed increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(88 citation statements)
references
References 21 publications
2
82
0
Order By: Relevance
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…29,34,35,[37][38][39][80][81][82][83][84][85][86][87][88][89] Nine interventions were delivered in the USA, all associated with the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC). [80][81][82][83][84][85][86][87]89 Five papers related to UK-based interventions 34,35,[37][38][39]88 and one intervention was delivered in Canada. 29 Studies were included if they pertained to a model of BFPS that included planned one-to-one contact between a mother and a peer supporter, reported breastfeeding rates (initiation, continuation or exclusivity) as an outcome measure and if they had been delivered in a developed country setting.…”
Section: Rapid Evidence Reviewmentioning
confidence: 99%
“…Eleven studies were RCTs, 29,34,35,37,80,81,84,[86][87][88][89] three were area-based controlled studies 38,82,83 and two were natural experiments. 39,85 Applying Cochrane risk of bias criteria, 91 we found that only three studies had a low risk of bias.…”
Section: Study Qualitymentioning
confidence: 99%
See 3 more Smart Citations